Coordination of precision grip in 2–6 years-old children with autism spectrum disorders compared to children developing typically and children with developmental disabilities - David, Fabian J.; Baranek, Grace T.; Wiesen, Chris; Miao, Adrienne; Thorpe, Deborah E. (Frontiers in Integrative Neuroscience, 2012)
Impaired motor coordination is prevalent in children with Autism Spectrum Disorders (ASD) and affects adaptive skills. Little is known about the development of motor patterns in young children with ASD between 2 and 6 years of age. The purpose of the current study was threefold: 1) to describe developmental correlates of motor coordination in children with ASD, 2) to identify the extent to which motor coordination deficits are unique to ASD by using a control group of children with other developmental disabilities (DD), and 3) to determine the association between motor coordination variables and functional fine motor skills. Twenty-four children with ASD were compared to 30 children with typical development (TD) and 11 children with DD. A precision grip task was used to quantify and analyze motor coordination. The motor coordination variables were two temporal variables (grip to load force onset latency and time to peak grip force) and two force variables (grip force at onset of load force and peak grip force). Functional motor skills were assessed using the Fine Motor Age Equivalents of the Vineland Adaptive Behavior Scale and the Mullen Scales of Early Learning. Mixed regression models were used for all analyses. Children with ASD presented with significant motor coordination deficits only on the two temporal variables, and these variables differentiated children with ASD from the children with TD, but not from children with DD. Fine motor functional skills had no statistically significant associations with any of the motor coordination variables. These findings suggest that subtle problems in the timing of motor actions, possibly related to maturational delays in anticipatory feed-forward mechanisms, may underlie some motor deficits reported in children with ASD, but that these issues are not unique to this population. Further research is needed to investigate how children with ASD or DD compensate for motor control deficits to establish functional skills.